PENGARUH APE KREASAGU (KREASI AMPAS SAGU) TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK ANANDA DESA BANTAN AIR KECAMATAN BANTAN KABUPATEN BENGKALIS - Nirdayu Ulfa; Ilga Maria; Novidawaty Tambunan (STKIP Subang, 2026)
This research is motivated by the low fine motor skills of children aged 4-5 years at ANANDA Kindergarten, Bantan Air Village due to the limitations of conventional learning media. On the other hand, Bengkalis Regency has abundant sago pulp waste potential that has not been optimally utilized. This study aims to test and analyze the effect of the use of Educational Game Tools (APE) KREASAGU (Sago Pulp Creation) on improving fine motor skills of children aged 4-5 years at ANANDA Kindergarten, Bantan Air Village. The research method used is quantitative experiment with a pre-experimental design in the form of One-Group Pretest-Posttest Design. The research subjects were 19 children aged 4-5 years. Data collection was carried out through direct participatory observation using a rating scale instrument. Data were analyzed using the Shapiro-Wilk normality prerequisite test and the paired sample t-test hypothesis test with the help of IBM SPSS version 26. The results showed a significant increase in children's fine motor skills. Before treatment (pretest), children's fine motor skills were in the Beginning to Develop (MB) category with an achievement of 41.17%. After being given treatment (posttest), the achievement jumped drastically by 80.83% and entered the Very Well Developed (BSB) category. The results of the paired sample t-test obtained a t-count value of 22.992 > t-table 2.101 with a significance value of 0.000 (<0.05), so H0 was rejected and Ha was accepted. The Normalized Gain (N-Gain) test value was 67.41% which was included in the moderate to high criteria. In conclusion, the use of APE KREASAGU media had a real and effective effect in improving the fine motor skills of early childhood.